Beyond deportation : the role of prosecutorial discretion in immigration cases - Wadhia, Shoba Sivaprasad; Wildes, Leon (New York : New York University Press, 2016)
When Beatles star John Lennon faced deportation from the U.S. in the 1970s, his lawyer Leon Wildes made a groundbreaking argument. He argued that Lennon should be granted 'nonpriority' status pursuant to INS's (now DHS's) policy of prosecutorial discretion. In U.S. immigration law, the agency exercises prosecutorial discretion favourably when it refrains from enforcing the full scope of immigration law. A prosecutorial discretion grant is important to an agency seeking to focus its priorities on the 'truly dangerous' in order to conserve resources and to bring compassion into immigration enforcement. The Lennon case marked the first moment that the immigration agency's prosecutorial discretion policy became public knowledge. Today,the concept of prosecutorial discretion is more widely known. This text examines this topic.
Previously issued in print: 2015.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 12, 2016).
Keywords: Deportation -- United States; Emigration and immigration law -- United States; Prosecution -- United States -- Decision making; Law; Migration, immigration & emigration; International relations; Laws of specific jurisdictions & specific areas of law; Constitutional & administrative law: general; Citizenship & nationality law